The effect of oil rent on social capital in OPEC member countries: Threshold panel approach - Zahra Dirkvand; Younes Nademi; Reza Maaboudi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2023)
Due to the heavy reliance on oil revenue in oil-exporting countries, fluctuations in oil prices can impact the social behavior of individuals within society. As a result, it appears that social capital, as a process of social institutions, is affected by oil rent. The purpose of this research is to investigate the impact of oil rent on social capital in selected OPEC oil-exporting countries from 2009 to 2020 using the threshold panel method. The findings indicate that the threshold value for the ratio of oil rent to GDP is estimated at 3.4%. Prior to this threshold, the ratio of oil rent to GDP had a positive and significant effect on social capital; however, after surpassing this threshold, the ratio of oil rent had a negative and significant effect on social capital. Inflation also had a non-linear effect on social capital, while government size did not have a significant impact. Based on these results and the detrimental effects of high levels of oil rent on social capital, it is necessary to control methods that divert oil resources towards rent-seeking activities. One solution could be removing control over oil rent from governments and transferring it directly to citizens. Experience with government management of oil has shown that instead of optimal allocation, most funds have been spent destructively; therefore, mismanagement has turned this divine gift into a curse.